Association of polymorphisms in the CRP gene with circulating C-reactive protein levels and cardiovascular events. - Lange, Leslie A; Carlson, Christopher S; Hindorff, Lucia A; Lange, Ethan M; Walston, Jeremy; Durda, J Peter; Cushman, Mary; Bis, Joshua C; Zeng, Donglin; Lin, Danyu; Kuller, Lewis H; Nickerson, Deborah A; et al. (JAMA, 2006)
CONTEXT: C-reactive protein (CRP) is an inflammation protein that may play a role in the pathogenesis of cardiovascular disease (CVD). OBJECTIVE: To assess whether polymorphisms in the CRP gene are associated with plasma CRP, carotid intima-media thickness (CIMT), and CVD events. DESIGN, SETTING, AND PARTICIPANTS: In the prospective, population-based Cardiovascular Health Study, 4 tag single-nucleotide polymorphisms (SNPs) (1919A/T, 2667G/C, 3872G/A, 5237A/G) were genotyped in 3941 white (European American) participants and 5 tag SNPs (addition of 790A/T) were genotyped in 700 black (African American) participants, aged 65 years or older, all of whom were without myocardial infarction (MI) or stroke before study entry. Median follow-up was 13 years (1989-2003). MAIN OUTCOME MEASURES: Baseline CIMT; occurrence of MI, stroke, and CVD mortality during follow-up. RESULTS: In white participants, 461 incident MIs, 491 incident strokes, and 490 CVD-related deaths occurred; in black participants, 67 incident MIs, 78 incident strokes, and 75 CVD-related deaths occurred. The 1919T and 790T alleles were associated with higher CRP levels in white and black participants, respectively. The 3872A allele was associated with lower CRP levels in both populations, and the 2667C allele was associated with lower CRP levels in white participants only. There was no association between CIMT and any CRP gene polymorphism in either population. In white participants, the 1919T allele was associated with increased risk of stroke for TT vs AA (hazard ratio [HR], 1.40; 95% confidence interval [CI], 1.06-1.87) and for CVD mortality (HR, 1.40; 95% CI, 1.10-1.90). In black participants, homozygosity for the 790T allele was associated with a 4-fold increased risk of MI compared with homozygosity for the 790A allele (95% CI, 1.58-10.53). The minor alleles of the 2 SNPs associated with lower plasma CRP concentration in white participants (2667C and 3872A) were associated with decreased risk of CVD mortality. CONCLUSIONS: Genetic variation in the CRP gene is associated with plasma CRP levels and CVD risk in older adults.
Keywords: African Continental Ancestry Group; Aged; C-Reactive Protein; Cardiovascular Diseases; Carotid Arteries; European Continental Ancestry Group; Female; Genotype; Humans; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Proportional Hazards Models; Risk; Stroke; Tunica Intima